The origin and evolution of investment treaty standards stability, value, and reasonableness - Ortino, Federico (Oxford, United Kingdom Oxford University Press, 2019)
This book provides a conceptual and legal analysis of the core of investment protection guarantees that emerge from international treaties signed since 1959 for the promotion and protection of foreign investment. It focuses on both the origin and evolution of investment treaty standards. In terms of origin, the work considers the broader context at the time when the first modern investment treaty was concluded. In terms of evolution, the work examines (a) the many decisions of ad hoc arbitral tribunals that have been called upon to apply these treaties in order to resolve the several hundred investor-State disputes, as well as (b) some of the recent investment treaties that in the past ten to fifteen years have attempted to clarify and/or reform the content and scope of investment protection guarantees. This study posits that the key investment protection provisions in investment treaties (and thus much of the related controversy) revolve around three distinct concepts: legal stability, investment's value and reasonableness. This book advances two main arguments. First, from the very beginning, the protection afforded to foreign investments by modern investment treaties has been an exceptionally broad one and as such restrictive of the host State's ability to regulate. Second, while a growing number of investment treaty tribunals as well as new investment treaties have to some extent reined in such broad protections, the evolution of key investment protection standards has been (and in many ways still is) marred by inconsistency and uncertainty.
Introduction -- Conclusion. Guarantees of legal stability in the strict sense -- Protecting the value of investments : the expropriation provision -- Ensuring reasonableness in the conduct of host states -- Introduction -- Guarantees of legal stability in the strict sense --
Includes bibliographical references (pages 177-183) and index.
Keywords: Investments, Foreign (International law) -- Electronic books; Investments, Foreign (International law)